Gambaran Klinikopatologi pada Respon Kemoterapi Neoadjuvan Triple Negative Breast Cancer di Rumah Sakit Umum Pusat Dr. Hasan Sadikin - Savitri, Widya; Surjawathy Hernowo, Bethy; Suryanti, Sri (Perhimpunan Dokter Spesialis Patologi Anatomik Indonesia (PDSPA), 2022)
BackgroundTriple Negative Breast Cancer (TNBC) accounts for 9-17% of all breast cancer diagnoses. TNBC has a high proliferation index and a poor prognosis with a higher response rate to neoadjuvant chemotherapy, but does not correlate with Overall Survival (OS) due to chemoresistence in more than 50% of TNBC. Neoadjuvant chemotherapy with anthracycline (doxorubicin) based regimens in combination with fluorouracil and cyclophosphamide (FAC) is still an option for TNBC. The aim of this study was to determine association between clinicopathological profile and response to neoajuvan chemotherapy in TNBC at Dr. Hasan Sadikin Bandung which is a referral hospital in West Java.MethodsThis study used an analytic observational method with a cross-sectional design. The research sample consisted of 40 TNBC cases from January 2017 to December 2019 at Dr. Hasan Sadikin hospital. Data obtained from medical records and archives of the Anatomical Pathology Laboratory consist of clinical response to neoadjuvant chemotherapy, age, tumor size, lymph node metastases and distant metastases, clinical stage, type of histopathology and lymphovascular vessel invasion.ResultsIn 40 cases of TNBC, 20 cases responded and 20 cases did not respond to neoadjuvant chemotherapy. In the non-response group, there were 90% of cases with histopathologic type invasive carcinoma of no special type and 75% showed invasion of lymphovascular vessels. There were no significant differences in age, tumor size, lymphovascular vessel invasion, stage, or histopathological type in the response and non-response groups.ConclusionThere is no correlation between clinicopathological features and neoadjuvant chemotherapy response in the case of Triple Negative Breast Cancer (TNBC). This can be caused by other factors including high heterogeneous tumor microenvironment (TME).